Political Representation in the Ancien Régime
1 online resource (362 pages)
Keywords: What kind of political representation existed in the Ancien Régime? Which social sectors were given a voice, and how were they represented in the institutions? These are some of the issues addressed by the authors of this book from different institutional angles (monarchies and republics; parliaments and municipalities), from various European territories and finally from a connected and comparative perspective.The aim is twofold: analyse the different mechanisms of political representation before Liberalism, their strengths and limitations; value the processes of oligarchisation and the possible mismatch between a libertarian model and a reality which was far from its idealised image.